Magnetic Properties of Tetragonal SmFe12−xMox Alloys in Bulk and Melt‐Spun Ribbons. Issue 15 (28th April 2022) - Rodríguez-Crespo, Bosco; Garcia-Franco, Andrés; Rosero-Romo, James Janderson; Echevarria-Bonet, Cristina; Porro, Jose Maria; Saiz, Paula G.; Salazar, Daniel
Abstract : Currently, electric motors and generators use high‐energy permanent magnets based on RE2 Fe14 B phases (RE: rare earth) with high amounts of RE often including heavy‐RE metals (Dy, Tb), the most critical group of the raw materials. REFe12 alloys are seen as potential alternatives to RE2Fe14B because they contain a significantly lower amount of RE metals with similar or better values of remanent magnetization ( M R ) and high magnetocrystalline anisotropy, which can give rise to a large energy product (BH)max . Herein, the effect of heat treatments on the coercivity and magnetic properties on melt‐spun ribbons of SmFe12− x Mo x ( x  = 0.5, 1) alloys with wheel speeds of 15 and 35 m s −1 is studied. The maximum coercivity after heat treatments is obtained in as‐spun ribbons at a speed of 35 m s −1 . For the x  = 0.5 ribbons, μ 0 H c increases from 0.06 to 0.36 T, while for the x  = 1.0 ones μ 0 H c is enhanced from 0.02 to 0.34 T. The highest values of saturation magnetization are obtained for the x  = 0.5 ribbons (≈145 Am 2  kg −1 ). Abstract : The effect of heat treatments on the coercivity and magnetic properties on melt‐spun ribbons of SmFe12− x Mo x ( x  = 0.5, 1) alloys is studied. The maximum coercivity is obtained in ribbons as‐spun at 35 m s −1 . For the x  = 0.5 ribbons, μ 0 H c increases from 0.06 to 0.36 T and the highest value of saturation magnetization is obtained for the x  = 0.5 ribbons (≈145 Am 2  kg −1 ).